Breast Mass with Bloody Discharge: A Case of Idiopathic Granulomatous Mastitis - AlSulaim, Lamees (International Journal of Innovative Research in Medical Science, 2022)
One of the rare identity of breast diseases is Idiopathic Granulomatous Mastitis (IGM), a chronic inflammatory breast condition that can mimic advanced breast cancer. The case came with nipple discharge and mass with skin changes, which was definitively diagnosed following core-cut biopsy of the mastitis group idiopathic granulomatous.